2018
DOI: 10.23956/ijermt.v6i6.260
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Deep Drawing Process

Abstract: Deep Drawing (DD) process is the one in which a punch forces a flat sheet metal blank into a die cavity.  DD can also be described as the process which involves conversion of flat thin sheet metal blanks into parts of desired shape. Little work is available in the applications of DD processes at elevated temperatures which is going to be a very important manufacturing application in the coming decades. Deep Drawing (DD) is one of the sheet metal forming processes widely used in automobile, aerospace, electroni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…As mentioned in the earlier section, the weight of an automobile can be reduced by replacing steel with an alternate material namely Aluminium.Cantor et al [7] and Toroset al [8] observed that depending on different regions and different manufacturing strategies wide range of aluminium alloys are applied in body panels. Based on features such as strength and formability, various alloys such as Heat treatable and non-heat treatable alloys are used in panels, developed from deep drawing process [9]. Further a survey is conducted on the available literature [10][11][12][13] w.r.t.…”
Section: Problem Statementmentioning
confidence: 99%
“…As mentioned in the earlier section, the weight of an automobile can be reduced by replacing steel with an alternate material namely Aluminium.Cantor et al [7] and Toroset al [8] observed that depending on different regions and different manufacturing strategies wide range of aluminium alloys are applied in body panels. Based on features such as strength and formability, various alloys such as Heat treatable and non-heat treatable alloys are used in panels, developed from deep drawing process [9]. Further a survey is conducted on the available literature [10][11][12][13] w.r.t.…”
Section: Problem Statementmentioning
confidence: 99%
“…According to results obtained again using DEFORM, the punch force required for drawing decreased as the pulse frequency was increased, and when the motion curve was limited to the drawing of the circular cup, the formability of the circular cup was enhanced, and the chance of breakage was reduced. Swapna, Rao, and Radhika, in 2017, performed circular cup drawing with stainless steel, brass, and high-strength low-alloy steel [9]. These materials were selected because most studies have used aluminum or magnesium alloys.…”
Section: Strengths Weaknesses Traditional Methodsmentioning
confidence: 99%
“…During deep drawing process, several defects may appear on the parts, mainly the fracture or tearing, wrinkling, and earing [ 47 ]. These defects can be the result of the process, material and geometric parameters [ 48 ].…”
Section: Manufacturing Processes For Aluminum Lithium Alloysmentioning
confidence: 99%